Speech by Brig. Gen. Dato' Prof. Dr. Kamarudin Hussin Vice Chancellor of UniMAP for Opening Ceramony IMT-GT “Academic & Research Exposition” (AREX) 2009 - Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event held at Dewan 2020, Kangar, Perlis.